Max Planck yearbook of United Nations law. - Frowein, Jochen Abr., 1934-; Wolfrum, Rüdiger; Philipp, Christiane, 1959- (Kluwer Law International, 1999)
In its third year, this text is a collection of essays by distinguished professors in international law. The essays cover a variety of topics, from the role of the Security Council to UN treaties, and from environmental issues to humanitarian law.